3 UTI Diagnosis and Management in the Over 65s According to Public Health England Guidelines. (6th February 2020) - Brice, H G T; Doherty, N; Biss, C; Quigley, T
Abstract: Introduction: The diagnosis of urinary tract infections (UTI) becomes increasingly difficult with age. Dipsticks are unreliable and with the prevalence of asymptomatic bacteriuria increasing to 17% in females over 75 even urine culture results can be unreliable. Public Health England (PHE) released new guidelines in November 2018 with criteria for diagnosing UTIs in the over 65s. Methods: Identify patients over 65 who are diagnosed with a UTI in Solihull acute medical unit. Collect data on presenting symptoms, dipstick and culture results and antibiotic use. Aim to improve guideline adherence and decrease dipstick use through education of medical and nursing staff via presentations and posters. Results: Prior to the educational intervention guideline adherence when diagnosing UTIs in over 65s was 55%. This rose to 82% following the educational intervention. Dipstick usage decreased from 49% to 28% following the intervention. Dipsticks were shown to be unreliable as 21.6% of dipstick positive urine samples sent for culture had a normal (0-80) white cell count in the laboratory, whilst 43.8% of dipstick negative urine samples sent for culture had a raised white cell count in the laboratory. On retrospective analysis 16.1% of patients treated for a UTI appeared to have had an asymptomatic bacteriuria. Co-amoxiclav was initially used for 51% of patients however there was resistance to Co-amoxiclav in 31% of samples where an organism was cultured. Conclusions: The educational intervention was able to increase PHE guideline adherence for diagnosing UTIs in the over 65s. There was also a decrease in the use of dipsticks which were shown to be unreliable in this age group. Prescribers remained reliant on broad-spectrum antibiotics with Co-Amoxiclav being most commonly used. This is likely to be ineffective in a significant number of patients given the common resistance seen in urine culture sensitivities.